PT Pertamina Patra Niaga Aviation Fuel Terminal (AFT) Syamsudin Noor Duta Duta Bahtera Program in Realizing Community-Based Sustainable Development Goals (SDG's) in Banjarbaru - Faidah Ramadhani; Dimas Budiman; Risky Diba Avrita; Amrizarois Ismail (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Duta Bahtera Program implemented by PT Pertamina Patra Niaga Aviation Fuel Terminal (AFT) Syamsudin Noor, Banjarbaru, is an initiative to reduce malnutrition rates through a community-based approach. This program involves multiple stakeholders, such as integrated health post cadres, parents, health centres and nutritionists in training activities, providing additional food, and socializing good parenting patterns. This is descriptive qualitative research to examine the implementation of the Duta Bahtera Program by PT Pertamina Patra Niaga AFT Syamsudin Noor, Banjarbaru and its relation to the Sustainability Development Goals (SDGs). The results of Duta Bahtera program showed that the program contributes significantly to public health and can be used as a model for similar programs in other areas. With effective collaboration and empowerment, this program creates a strong foundation for a healthier future for children in Indonesia. Thus, the Duta Bahtera Program has a role in supporting the achievement of Sustainable Development Goals (SDGs), especially in eradicate poverty (SDG 2), improving health and well-being (SDG 3), and empowering communities and building multi-party collaboration (SDGs 17). This program also shows efforts to maintain a balance between environmental sustainability, economic growth and community welfare as a symbol of achieving the Triple Bottom Line SDGs.